2020
DOI: 10.3390/app10062073
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Emissions from Brake Wear are the Major Source of Airborne Particulate Matter Bioaccumulated by Lichens Exposed in Milan (Italy)

Abstract: The concentration of selected trace elements and the magnetic properties of samples of the lichen Evernia prunastri exposed for 3 months in Milan (Italy) were investigated to test if magnetic properties can be used as a proxy for the bioaccumulation of chemical elements in airborne particulate matter. Magnetic analysis showed intense properties driven by magnetite-like minerals, leading to significant correlations between magnetic susceptibility and the concentration of Fe, Cr, Cu, and Sb. Selected magnetic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 48 publications
3
25
0
Order By: Relevance
“…Magnetic properties of tree leaves as biocarriers of the deposited atmospheric dust have been investigated in relation to air pollution by many authors [5][6][7][8][9][10][11][12][13][14][15][16][17]. There are also numerous studies on magnetic properties of tree needles [18][19][20], tree barks, rings or branches [21][22][23][24][25][26], lichens, in situ or transplanted [27][28][29][30][31][32][33][34], and moss and transplanted moss bags [32,[35][36][37][38][39][40][41][42]. High sensitivity of magnetic methods enabled even examination of magnetic properties of spider webs [43].…”
mentioning
confidence: 99%
“…Magnetic properties of tree leaves as biocarriers of the deposited atmospheric dust have been investigated in relation to air pollution by many authors [5][6][7][8][9][10][11][12][13][14][15][16][17]. There are also numerous studies on magnetic properties of tree needles [18][19][20], tree barks, rings or branches [21][22][23][24][25][26], lichens, in situ or transplanted [27][28][29][30][31][32][33][34], and moss and transplanted moss bags [32,[35][36][37][38][39][40][41][42]. High sensitivity of magnetic methods enabled even examination of magnetic properties of spider webs [43].…”
mentioning
confidence: 99%
“…However, the results of the present study, although preliminary, point out the feasibility of an investigation that would permit obtaining information on the health status of urban populations, combining high spatial density and low cost. Furthermore, recent investigations on other types of bioindicators have shown that there are measurements able to provide information on atmospheric metal pollution by means of other analytical techniques, even simpler and cheaper than atomic emission spectrometry, such as X-ray fluorescence [42][43][44] and magnetic analysis [45][46][47][48][49]. This would make the approach accessible to a large number of laboratories in terms of purchase and operating costs of equipment.…”
Section: Resultsmentioning
confidence: 99%
“…Mn, Cd and Ni may be associated with exhaust emissions [74][75][76]. Furthermore, such elements as Pb, Zn, Cu, Cd, Cr and Ni in TSP and PM1 are the markers of diesel engine exhaust, oil combustion, tire and brake abrasion, brake wear debris and burning of lubricating oil [77][78][79]. Simultaneously, Al along with Ti (and also Fe and Mn) are considered as crustal metals and their enhanced concentration can be an effect of road dust re-suspension and the local geology/soil composition [71,72].…”
Section: Concentration Of Potentially Toxic Elements and Their Sourcementioning
confidence: 99%
“…Mn, Cd and Ni may be associated with exhaust emissions [74][75][76]. Furthermore, such elements as Pb, Zn, Cu, Cd, Cr and Ni in TSP and PM1 are the markers of diesel engine exhaust, oil combustion, tire and brake abrasion, brake wear debris and burning of lubricating oil [77][78][79].…”
Section: Concentration Of Potentially Toxic Elements and Their Sourcementioning
confidence: 99%